AGN jets and winds in polarized light: the case of Mrk 231. Issue 2 (23rd July 2021) - Silpa, S; Kharb, P; O'Dea, C P; Baum, S A; Sebastian, B; Mukherjee, D; Harrison, C M
ABSTRACT: We present the results of a multifrequency, multiscale radio polarimetric study with the Very Large Array (VLA) of the Seyfert 1 galaxy and BALQSO, Mrk 231. We detect complex total and polarized intensity features in the source. Overall, the images indicate the presence of a broad, one-sided, curved outflow towards the south which consists of a weakly collimated jet with poloidal inferred magnetic fields, inside a broader magnetized 'wind' or 'sheath' component with toroidal inferred magnetic fields. The model of a kpc-scale weakly collimated jet/lobe in Mrk 231 is strengthened by its C-shaped morphology, steep spectral index throughout, complexities in the magnetic field structures, and the presence of self-similar structures observed on the 10-parsec-scale in the literature. The 'wind' may comprise both nuclear starburst (close to the core) and active galactic nuclei winds, where the latter maybe the primary contributor. Moving away from the core, the 'wind' component may also comprise the outer layers (or 'sheath') of a broadened jet. The inferred value of the (weakly collimated) jet production efficiency, ηjet ∼ 0.01, is consistent with the estimates in the literature. The composite jet and wind outflow in Mrk 231 appears to be low-power and matter-dominated, and oriented at a small angle to our line of sight.